Data on brain serotonergic activity in Premenstrual Dysphoria - Eriksson, Olle (Uppsala University, 2022)
Dataset investigating potential quantitative and qualitative differences in brain serotonergic activity between women with Premenstrual Dysphoria (PMD) and asymptomatic controls.

Positron-emission tomography with the immediate precursor of serotonin, 5-hydroxytryptophan (5-HTP), radiolabelled by 11C in the beta-3 position, was performed in the follicular and luteal phases for 12 women with PMD and 8 control women. Brain radioactivity–a proxym for serotonin precursor uptake and synthesis–was measured in 9 regions of interest (ROIs): the right and left sides of the medial prefrontal cortex, dorsolateral prefrontal cortex, putamen and caudate nucleus, and the single “whole brain”.

The dataset was originally published in DiVA and moved to SND in 2024.

Dataset avseende potentiella kvantitativa och kvalitativa skillnader i hjärnans serotonergiska aktivitet mellan kvinnor med premenstruell dysfori (PMD) och asymtomatiska kontrollpersoner. Se engelsk beskrivning för ytterligare info.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Data över hjärnans serotonergiska aktivitet vid Premenstruell Dysfori
Keywords: 5-Hydroxytryptophan; 5-hydroxytryptofan; Image Interpretation, Computer-Assisted; Datorstödd bildtolkning; Menstrual Cycle; Menstruationscykel; Positron-Emission Tomography; Positronemissionstomografi; Premenstrual Dysphoric Disorder; Premenstruellt dysforisk störning; gynaecology; gynekologi; reproductive health; reproduktiv hälsa; premenstrual syndrome; premenstruellt syndrom; Gynaecology, Obstetrics and Reproductive Medicine; Gynekologi, obstetrik och reproduktionsmedicin